THE ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS VIII SMPN 11 SINGKAWANG TIMUR: THE ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS VIII SMPN 11 SINGKAWANG TIMUR - Heny, Dwi Anggra; Kurniawan, Arif Didik; Qurbaniah, Mahwar (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
Based on the results of interviews with science teachers at SMPN 11 Singkawang Timur, that in class VIII students experience learning difficulties indicated by the existence of certain obstacles to achieving learning outcomes. The purpose of the study was to find out how the students' learning difficulties in science subjects in class VIII SMPN 11 Singkawang Timur. The method used in this research is a descriptive qualitative approach. Primary data sources were obtained from students in grades VIII A, VIII B, and VIII C of SMPN 11 Singkawang Timur. Meanwhile, secondary data sources were obtained from science teachers in class VIII and students in grades VIII A, VIII B, and VIII C of SMPN 11 Singkawang Timur. Data collection techniques using indirect communication, interviews and documentation. Data collection tools using a questionnaire sheet, interview guidelines. Data analysis techniques perform data collection, data reduction, data presentation, drawing conclusions. The results showed that students' learning difficulties in science subjects in class VIII of SMPN 11 Singkawang Timur were classically stated as moderate according to the results of the questionnaire scores obtained were interpreted as moderate with a percentage of 60.13%. The conclusion in this study is that when carrying out science learning students have learning difficulties with different percentages of each class, in class VIII A the questionnaire score of 61.23% is interpreted as high which states that learning difficulties in science are low, class VIII B the percentage is 59.13% moderately interpreted and grade VIII C with a percentage of 59.23% interpreted as being in accordance with the scores obtained by class VIII B and VIII C stating that students' learning difficulties in science subjects were moderate.